Refleksje na temat inkluzji. Rozprawa o ideologicznej sprzeczności, oczekiwaniach i poszukiwaniu sensu]. - Braumová, Zdeňka; Kliment, Pavel (Studia Edukacyjne, 2024)
Is it widely known what inclusion is? Is there a difference between inclusion and integration? There are many opinions and answers that reveal a low level of understanding. The certain elusiveness of inclusion is both an advantage and a pitfall. The ambiguity of interpretation allows for greater reflection and exploration. However, it also hinders society-wide understanding since meaning is only given to inclusion by individuals through a unique understanding tied to individual experience and context of meaning. We present here our take on the issue, deliberately raising questions without requiring strict answers, as an inspiration for welcome discussion and reflection.